2021
DOI: 10.1186/s12888-021-03347-3
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in personal recovery in individuals with psychotic disorders through hospitalisation in a psychiatric ward: preliminary findings

Abstract: Background This study aimed to investigate whether personal recovery indices in individuals with psychotic disorders would change through hospitalisation in a psychiatric ward and to identify factors associated with these changes. Methods Participants underwent assessments for personal recovery using the Questionnaire about the Process of Recovery, Recovery Assessment Scale, and Self-Identified Stage of Recovery Part A and B; clinical symptoms usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The themes of the current study ‘no symptom domination’, ‘regain functioning’, and ‘emotional stability’ validate the above findings. However, a recent meta-analysis on factors associated with recovery indicates personal recovery factors are not related to symptoms (Leendertse et al, 2021) and perception of personal recovery did not change although clinical symptoms improved during hospitalization (Mitsunaga-Ohmuro & Ohmuro, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The themes of the current study ‘no symptom domination’, ‘regain functioning’, and ‘emotional stability’ validate the above findings. However, a recent meta-analysis on factors associated with recovery indicates personal recovery factors are not related to symptoms (Leendertse et al, 2021) and perception of personal recovery did not change although clinical symptoms improved during hospitalization (Mitsunaga-Ohmuro & Ohmuro, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Third, the cross-sectional design of this study limited the significance of the findings. A previous study conducted in Japanese acute care wards that focused on medication [ 39 ] found no longitudinal changes in personal recovery. Therefore, the effects of personal narratives shared within psychosocial treatment interventions on personal recovery have not been examined and should be evaluated longitudinally.…”
Section: Discussionmentioning
confidence: 98%
“…However, most participants in the current study were hospitalized patients with relatively mild psychiatric symptoms who were participating in psychiatric rehabilitation. Decreased autonomy and decision-making in the inpatient setting have been noted in the past [ 39 ], and it is possible that the participants in this study were more controlled in terms of their environment. Along with the psychopathological heterogeneity of the participants, this environmental specificity may explain the difference between our results and previous findings.…”
Section: Discussionmentioning
confidence: 99%